Khamitova K.K., Kurbanova A.B., Ybyraeva A.B. Ecological estimation of natural water quality in Almaty and Almaty region: Al-Farabi kazakh national university, Kazakhstan, Almaty (Eurasian Journal of Ecology, 2018)
One of the main wealth of any state – the natural resources. Therefore, thepresent work is devoted to the study of natural water quality Almaty city andits environs. The problem of nature protection erectrank in state policy, so as toachieve political, economic and social objectives, facing society, it is necessarythe implementation of activities by rational use, protection and reproductionof natural resources. Currently, the problem of increasing the effectiveness ofenvironmental measures are of significant interest. In Kazakhstan, as we know,the vast majority of businesses require environmental support, which includesa wide range of engineering, medical and social measures, laws, programs andmeans of implementation. Questions greening processes and principled assessment of the impact of existing enterprises on the environment yet delivered andwaiting for his decision. In this connection monitoring studies in the laboratoryof natural reservoirs of water quality conditions ponderable importance in atstudy of the protection of water resources. In this article published the results ofstudies of the physical and organoleptic properties of water lakes of Almaty andAlmaty region – Sayran, Issyk, Big Almaty.Were also identified hydrogenousindicators, the amount of suspended substances, the iron content in the samplesof natural waters. Order to successfully implementation monitor the state of theenvironment, modern methods of analysis must be used. The study was conducted on the basis of published in various scientific editions methods of physical and chemical methods of research and the latest equipment. The resultsevaluated real opportunities impact man-made impacts on the hydrosphere, theeffectiveness of the existing environmental activities.Key words: Natural water, water quality, methods for determining thephysical and organoleptic properties of water, norms quality , indicatorsof water quality